2018
DOI: 10.1038/gim.2017.178
|View full text |Cite
|
Sign up to set email alerts
|

RET somatic mutations are underrecognized in Hirschsprung disease

Abstract: Somatic mutations of the RET gene are underrecognized in HSCR. Molecular investigation of the parents of patients with seemingly sporadic mutations is essential to determine recurrence risk in these families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…In short segment HD, where the aganglionic segment does not extend beyond the upper sigmoid (80% of the cases) a strong sex bias exists with more affected males (sex ration four male/one female). In this line, it was recently shown that mosaicism of RET mutations in HD is still underestimated [96]. The associated Waardenburg Fig.…”
Section: Adult Neural Crest-derived Stem Cells and Sex-specific Diffementioning
confidence: 95%
See 1 more Smart Citation
“…In short segment HD, where the aganglionic segment does not extend beyond the upper sigmoid (80% of the cases) a strong sex bias exists with more affected males (sex ration four male/one female). In this line, it was recently shown that mosaicism of RET mutations in HD is still underestimated [96]. The associated Waardenburg Fig.…”
Section: Adult Neural Crest-derived Stem Cells and Sex-specific Diffementioning
confidence: 95%
“…For further information regarding craniofacial defects related to NC malformation, see [66,94]. In this line, it was recently shown that mosaicism of RET mutations in HD is still underestimated [96]. However, the potential occurrence and impact of sex-specific differences in prevalence and severity of such neurocristopathies disease are still underestimated.…”
Section: The Role Of Sex In Neuronal Development and Neural Stem Cellmentioning
confidence: 99%
“…In the past few years, the identification of novel susceptibility genes and variants for HSCR was based on the use of GWAS,GWES and next‐generation sequencing (NGS) approaches . All of them have fairly improved our knowledge about the genetic background of the disease.…”
Section: Other Genes and Susceptibility Locimentioning
confidence: 99%
“…In the past few years, the identification of novel susceptibility genes and variants for HSCR was based on the use of GWAS,GWES 20,25,[38][39][40][154][155][156][157][158][159][160][161] and next-generation sequencing (NGS) approaches. [162][163][164][165][166][167][168][169][170] All of them have fairly improved our knowledge about the genetic background of the disease. For instance, a recent GWAS has described that testis-specific A13 genetic variants (a potential susceptible locus in TCA) may affect the extent of aganglionosis during ENS development.…”
Section: New Approachesmentioning
confidence: 99%
“…To the Editor: We read "RET Somatic Mutations Are Underrecognized in Hirschsprung Disease," by Jiang et al 1 , recently published in your journal, with great interest. The authors hypothesize a contribution of RET somatic mutations to Hirschsprung disease (HSCR).…”
mentioning
confidence: 99%